CT evaluation of anatomical variations of paranasal sinus region and their clinical importance - Tiwari, Tapendra Nath; Kardam, Narendra Kumar (International Journal of Research in Medical Sciences, 2019)
Background: Paranasal sinuses are air filled spaces present within the skull and facial bones. Paranasal sinuses region anatomy is highly variable. Knowledge of these variations is very important for radiologists as well as endoscopic surgeons for preoperative evaluation to avoid damage to adjacent vital structures. CT is the best modality to delineate the sinus anatomy as well as soft tissue structures. Thus, this study was undertaken to evaluate the anatomical variations of paranasal sinus region and ascertain their clinical importance. Methods: A total of 142 patients, those referred from various outdoor/indoor departments with the symptoms related to nose and paranasal sinuses were included. Detailed history, appropriate clinical examinations, biochemical investigations and X-ray PNS were recorded. Unenhanced CT scan of the PNS was performed for these patients in the axial planes and reformatted coronal planes. Observation was made and analysed using descriptive tools and scientific methods. Results: Deviated nasal septum was the most common variation followed by middle concha bullosa, Paradoxical middle turbinate, curved uncinate process, overpneumatized ethmoidal bulla, superior concha bullosa, prominent Agger Nasi cells, haller cells, onodi cells, maxillary sinus septae and pneumatization of uncinate process. Incidence of anatomical variation was 75% among the patients showing PNS mucosal changes while it was 94% among patients showing no mucosal changes. Chi square statics revealed that presence of anatomical variation does not mean a predisposition to mucosal changes. Conclusions: The presence of anatomical variants does not indicate predisposition to sinus pathology but may predispose to increased risk of intraoperative complications. It is important to pay close attention to anatomical variations in the preoperative evaluation to avoid possible complications.